Behind and beyond the pediatric metabolic syndrome - Brambilla Paolo; Pietrobelli Angelo (BMC, 2009)
Abstract The growing use of the Metabolic Syndrome in pediatric age need a critical approach, on the basis of recent concerns on definition and usefulness for individual management in clinical practice. We reviewed these aspects from a pediatric point of view, providing a set of questions about what the Metabolic Syndrome means in a clinical setting. The new proposed pediatric definition by IDF was discussed, by outlying how it does not fully consider the peculiarities of children and adolescents. The comparison between two cases of obese children was used in order to show how this diagnosis could be confusing for a correct management. We stressed the need for health-related limits for each component of the Metabolic Syndrome instead of percentile-derived cut-points, as well as the opportunity to extend the estimation to other family or individual risk factors by means of a multiple-items screening form. In conclusion, Metabolic Syndrome use in pediatric age suffers at present from important limitations (i.e., adult derived definition, possibility to rule-in but not to rule-out the individual metabolic risk, instability of MetS during adolescence, poor usefulness of the diagnosis for specific treatment). Consequently, a prudent use of Metabolic Syndrome for children and adolescents seems to be the best and honest position for paediatricians, waiting for long term, longitudinal follow-up studies that could clarify the entire question.